Constructing local environmental agendas - "Buckingham - Hatfield, Susan (ed.)" (London, 1999)
Constructing Local Environmental Agendas draws on original contributions from specialists worldwide to argue that there is scope for local areas to improve their environments, provided local people are involved. International case studies, from UK, Europe, Australia, Pakistan and Sri Lanka, demonstrate the importance of respect for indigenous knowledge and the need to remove layers of bureaucracy from policy making.
Keywords: Environmental policy